Measurement of the Developing Foot in Shod and Barefoot Paediatric Populations: A Narrative Review - Maisie Squibb; Kelly Sheerin; Peter Francis (Children, 2022)
The theory that footwear may change foot shape dates back 100 years. Since this period, research has revealed the anatomical and functional consequences that footwear can cause to the foot. Children’s feet remain malleable as they undergo developmental changes until adolescence, which is why childhood is arguably a crucial period to understand how footwear can affect natural foot development. This review explored the development of the foot in children and adolescents and the methods used to measure the different foot structures; it comments on the key issues with some of these methods and gives direction for future research. Various internal and external factors can affect foot development; the main factors are age, gender, ethnicity, body mass index (BMI) and footwear habits. Research on how footwear can affect foot development has increased over the years and the final section of this review aimed to unpick the findings. Studies investigating the influence of footwear habits on foot length and width have established inconsistent findings. Many of the studies in the review did not control for internal and external factors that can affect foot development. There was also a limited number of studies that investigated hallux valgus angle and muscle strength differences in those with different footwear habits. Moreover, multiple studies in the final section of this review did not successfully examine the footwear habits of the participants and instead used observations or self-assessments, which is a major limitation. Future research should examine footwear behaviors and other confounding factors when investigating the development of the foot in children and adolescents. Moreover, researchers should critically evaluate the methods used to quantify the different structures of the foot to ensure valid and reliable parameters are being used.